Administration of the KCa channel activator SKA-31 improves endothelial function in the aorta of atherosclerosis-prone mice - Vera, O. Daniel; Mishra, Ramesh C.; Khaddaj-Mallat, Rayan; Hamm, Liam; Almarzouq, Barak; Chen, Yong-Xiang; Belke, Darrell D.; Singh, Latika; Wulff, Heike; Braun, Andrew P. (Frontiers in Pharmacology, 2025)
IntroductionAtherosclerosis remains a major risk factor for vascular dysfunction and cardiovascular (CV) disease. Pharmacological enhancement of endothelial Ca2+-activated K+ channel activity (i.e., KCa2.3 and KCa3.1) opposes vascular dysfunction associated with ageing and type 2 diabetes (T2D) in ex vivo and in vivo preparations. In the current study, we have investigated the efficacy of this strategy to mitigate endothelial dysfunction in the setting of atherogenesis.MethodsMale apolipoprotein E knockout (Apoe−/−) mice fed a high fat diet (HFD) were treated daily with the KCa channel activator SKA-31 (10 mg/kg), the KCa3.1 channel blocker senicapoc (40 mg/kg), or drug vehicle for 12-weeks. Endothelium-dependent and -independent relaxation and vasocontractility were measured in abdominal aorta by wire myography. The development of atherosclerosis in the thoracic aorta was characterized by Oil Red O staining and immunohistochemistry. Key vasorelaxant signaling proteins were quantified by q-PCR.ResultsEndothelium-dependent relaxation of phenylephrine-constricted aortic rings was impaired in Apoe−/− HFD mice (53%) vs. wild-type (WT) controls (80%, P < 0.0001), consistent with endothelial dysfunction. Treatment of Apoe−/− HFD mice with SKA-31, but not senicapoc, restored maximal relaxation to the WT level. Phenylephrine-evoked contraction was similar in WT and vehicle/drug treated Apoe−/− mice, as was the maximal relaxation induced by the endothelium-independent vasodilator sodium nitroprusside. mRNA expression for eNOS, KCa3.1, KCa2.3 and TRPV4 channels in the abdominal aorta was unaffected by either SKA-31 or senicapoc treatment. Fatty plaque formation, tissue collagen, α-smooth muscle actin and resident macrophages in the aortic sinus were also unaltered by either treatment vs. vehicle treated Apoe−/− HFD mice.ConclusionOur data show that prolonged administration of the KCa channel activator SKA-31 improved endothelial function without modifying fatty plaque formation in the aorta of Apoe−/− mice.